Atypical renal presentation of antiphospholipid syndrome - Gaspar, A (2017)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease which can occur as a primary disease or in association with other autoimmune diseases, the most frequent being Systemic Lupus Erythematosus (SLE). Although renal manifestations of SLE are well known, antiphospholipid syndrome renal manifestations such as antiphospholipid syndrome nephropathy and glomerulopathies have yet to be better characterized. The authors present the case of a 39 -year -old Caucasian woman with antiphospholipid syndrome diagnosis and a previous history of deep venous thrombosis and intermittent polyarthralgia, who was referred to a nephrology consultation for proteinuria and microscopic haematuria with preserved renal function. The renal biopsy showed a pattern of membranous glomerulopathy and thrombotic microangiopathy in association with antiphospholipid syndrome nephropathy. This case report illustrates a complex clinical and anatomopathological case of a 39 - year -old woman with a previous antiphospholipid syndrome diagnosis who presented with unspecific manifestations such as proteinuria and microscopic haematuria and preserved renal function. The histological findings alert us to the range of possible renal manifestations of APS and the need to better characterize these patients by preforming renal biopsy.